Joshua - Sharp, Carolyn J. (Smyth & Helwys bible commentary, 2019)
"The book of Joshua is rich, brimming with dramatic irony, heart-pounding conflict, and luminous stories of miracles. But Joshua presents serious challenges for theological ethics, giving us a deity who demands militarized appropriation of indigenous territory and extermination of Canaanite noncombatants. In this commentary, Carolyn Sharp explores archaeological, literary, theological, and ethical dimensions of Joshua in depth. Sharp honors indigeneity on every page of her commentary, supplying postcolonial epigraphs, quotations of ancient Canaanite voices, and twenty-nine sidebars with insights from Native Studies. Dozens of side- bars offer suggestions for the Christian preacher. This volume is essential for those seeking to engage fruitfully with violent traditions in Scripture."--